Comparative transcriptome analysis of compatible and incompatible Brassica napus—Xanthomonas campestris interactions - Yang, Li; Zhao, Chuanji; Bai, Zetao; Yang, Lingli; Schranz, M. Eric; Liu, Shengyi; Bouwmeester, Klaas (Frontiers in Plant Science, 2022)
Black rot caused by the vascular pathogenic bacterium Xanthomonas campestris pv. campestris (Xcc) is widespread in Brassicaceae plants and an infectious disease that causes large yield losses in oil seed rape (Brassica napus L.). Improvement of resistance through breeding is a crucial strategy to prevent black rot disease in B. napus, but presently hampered by insufficient understanding of Xcc-Brassica interactions. This study compares two EMS-mutagenized B. napus lines that show contrasting resistance levels to their susceptible progenitor. Patterns of differential gene expression between these B. napus lines were evaluated at three time points post inoculation by comparative RNA-seq analysis. In line with the observed disease phenotypes, the susceptible line ZS9mXccS-1 displayed a steady amount of differentially expressed genes (DEGs) at different time points of infection, whereas the resistant line ZS9mXccR-1 displayed a gradual increase in DEGs throughout the course of infection. Weighted gene co-expression network analysis (WGCNA) pinpointed multiple defense-related hub genes with potential central roles in immunity, including the cell surface receptor genes CRK11 and BIR1, and the associated downstream regulatory genes WRKY11 and PBL30. KEGG analysis of DEGs belonging to two distinct co-expression modules revealed enriched pathways associated with defense, including Ca2+-signalling, receptor-mediated immunity, and phytohormone balance. Taken together, our comparative transcriptome analysis provides new avenues to unravel the mechanisms underlying black rot resistance in B. napus.